Roots, dimensions and limits of the concept of tolerance - Giusti, Miguel (Estudios de Filosofía, 2008)
I will try to argue that tolerance, although it is essentially linked to the experience of an original conflict, is a parasitic notion, that is, that it always depends on a prior ethical conception from which it derives its strength or positive meaning; and I will advocate for framing the understanding of tolerance within the paradigm of recognition. To do this, I will divide my argument into two parts. In the first place, I will try to select what I consider the main hermeneutical matrices of the notion of tolerance, with the idea of ​​showing the double conceptual game to which I have just alluded, and with the purpose of gradually drawing a conceptual map of the terrain that notion covers. Secondly, I will propose a summary systematic synthesis of the notion of tolerance, describing the features that, it seems to me, are constitutive, among them precisely that of being a parasitic notion. It will not be a mere reconstruction, but rather an attempt to show a propositional sense that makes the defense of this virtue plausible.